Модель прогнозу для даних про продажі на основі керованих веб-сервісів AMAZON - Юр’єв, Я. В. (ХНУРЕ, 2022)
This paper describes the use of machine learning to predict data and the use of artificial intelligence algorithms to predict sales. To achieve this goal, it is proposed to use Amazon services: SageMaker (machine learning modeling and placement service) and Forecast (high-precision forecasting service based on machine learning technologies).